A process for building the capacity of informal science education providers to engage Latinos - Sorensen, Erica Kathryn, author; Bruyere, Brett L., advisor; Balgopal, Meena, advisor; Teel, Tara L., committee member (Colorado State University. Libraries, 2010)
The challenges of our global economy and escalating environmental concerns are fueling the demand for qualified graduates in science, technology, engineering, and mathematics (STEM) fields. However, the U.S. now lags behind many other industrialized nations in science achievement. Furthermore, educators have been struggling to close the gap in science achievement between White and non-White students in this country for decades. Considering the rapid demographic changes occurring in the U.S., improving science education for all students has become a critical priority. Latinos are the largest and fastest growing ethnic group in the United States, yet Latino students remain at the margins of STEM education and are underrepresented in these fields in the workforce. Informal science education (ISE) is science learning that occurs outside of formal classrooms in settings such as museums, zoos, science and nature centers, and other community-based youth development programs. ISE programs can have many academic and social benefits for participants and play an important role in improving science education, yet they often face challenges in engaging Latinos and other diverse youth and families. The challenges of our global economy and escalating environmental concerns are fueling the demand for qualified graduates in science, technology, engineering, and mathematics (STEM) fields. However, the U.S. now lags behind many other industrialized nations in science achievement. Furthermore, educators have been struggling to close the gap in science achievement between White and non-White students in this country for decades. Considering the rapid demographic changes occurring in the U.S., improving science education for all students has become a critical priority. Latinos are the largest and fastest growing ethnic group in the United States, yet Latino students remain at the margins of STEM education and are underrepresented in these fields in the workforce. Informal science education (ISE) is science learning that occurs outside of formal classrooms in settings such as museums, zoos, science and nature centers, and other community-based youth development programs. ISE programs can have many academic and social benefits for participants and play an important role in improving science education, yet they often face challenges in engaging Latinos and other diverse youth and families.
Department Head: Michael J. Manfredo.